Auditor Experience and Fraud Detection Capability: Does Gender Still Matter? Evidence from Public Accounting Firms in Indonesia - Fujianti, Lailah; Waskito, Meindro; Patriandari, Patriandari; Rianto, Rianto (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Financial statement fraud remains a persistent challenge for the auditing profession, especially in developing countries amid governance dynamics. Auditors’ capacity to detect fraud hinges on professional competence, notably audit experience. Yet findings on how auditor gender interacts with experience to influence fraud-detection capability are inconsistent. This study investigates the effect of auditor experience on financial statement fraud detection capability and tests whether this effect differs between male and female auditors. Employing a causal design, we integrate Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with Multi-Group Analysis (MGA) to assess gender differences. Data were collected via questionnaires from 78 auditors employed by accounting firms in Jakarta, Indonesia, using cluster random sampling. Results show that auditor experience exerts a positive and significant impact on fraud detection capability for both genders. This supports the view that experience functions as a professional learning mechanism, strengthening judgment, heightening sensitivity to fraud red flags, and improving fraud-risk assessment quality. However, the MGA-PLS analysis reveals no gender difference in the strength of the experience–fraud detection relationship. The findings imply that established auditing standards, rigorous documentation, and layered supervision may mitigate gender-based disparities in auditing practice, promoting comparable fraud-detection performance across male and female auditors globally.